Survey of the Effects of a Column for Adsorption of β2‐Microglobulin in Patients With Dialysis‐Related Amyloidosis in Japan. Issue 1 (20th November 2012) - Gejyo, Fumitake; Amano, Izumi; Ando, Tetsuo; Ishida, Mari; Obayashi, Seiichi; Ogawa, Hiroshi; Ono, Toshihiko; Kanno, Yutaka; Kitaoka, Tateki; Kukita, Kazutaka; Kurihara, Satoshi; Sato, Motoyoshi; et al.
Abstract Dialysis‐related amyloidosis is a serious complication of long‐term hemodialysis. Its pathogenic mechanism involves accumulation of β2‐microglobulin in the blood, which then forms amyloid fibrils and is deposited in tissues, leading to inflammation and activation of osteoclasts. Lixelle, a direct hemoperfusion column for adsorption of β2‐microglobulin, has been available since 1996 to treat dialysis‐related amyloidosis in Japan. However, previous studies showing the therapeutic efficacy of Lixelle were conducted in small numbers of patients with specific dialysis methods. Here, we report the results of a nationwide questionnaire survey on the therapeutic effects of Lixelle. Questionnaires to patients and their attending physicians on changes in symptoms of dialysis‐related amyloidosis by Lixelle treatment were sent to 928 institutions that had used Lixelle, and fully completed questionnaires were returned from 345 patients at 138 institutions. The patients included 161 males and 184 females 62.9 ± 7.7 years age, who had undergone dialysis for 25.9 ± 6.2 years and Lixelle treatment for 3.5 ± 2.7 years. Based on self‐evaluation by patients, worsening of symptoms was inhibited in 84.9–96.5% of patients. Of the patients, 91.3% felt that worsening of their overall symptoms had been inhibited, while attending physicians evaluated the treatment as effective or partially effective for 72.8% of patients. Our survey showed that Lixelle treatment improved symptoms or prevented the progression of dialysis‐related amyloidosis in most patients.